Efektivitas Ampas Tahu Sebagai Adsorben Logam Tembaga Pada Air Limbah Industri - Dahlia Rosma Indah; Husnul Hatimah; Hulyadi Hulyadi (Hydrogen: Jurnal Kependidikan Kimia, 2021)
Copper is one of the toxic metals for health and the environment. In humans, high doses of copper metal can cause vomiting, dizziness, weakness, kidney and liver symptoms, anemia, to coma, and in severe cases, the patient can die. Judging from the dangers, proper waste management is needed to reduce the side effects of these pollutants. A practical and inexpensive technology is an adsorption adsorption technique using an efficient and easily available natural adsorbent, namely tofu dregs. The protein contained in tofu is one of the reasons for using tofu waste as an adsorbent. The absorption of amino acids that form two-charged ions (zwitter ions) is owned by proteins. Toxic metal can be bound to protein as metallotionein. The study consisted of four stages, namely (1) Analysis of initial copper content in silver craft waste; (2) Preparation of tofu waste adsorbent; (3) Characterization of tofu dregs adsorbent; and (4) variation of adsorption contact time. The study used a laboratory-scale experimental method. The adsorbent was contacted with the sample using a magnetic stirrer at various times. Instrument Atomic Absorption Spectrometer was used for the analysis of copper metal content and identification of its functional groups using an infrared spectrometer with the result that tofu waste has functional groups -OH, NH (stretching), CH (aliphatic), C=O, -OH (bending vibrations). , and CO. Copper metal content obtained is 19.5979 ppm. The optimum adsorption time was reached at 120 minutes with an optimum adsorption efficiency of 54.88%.